Learning Styles in Differentiated Learning of Water Cycle Material for Grade V Elementary School - Nurrizka, Thania; Ulia, Nuhyal (Universitas Muhammadiyah Sumatera Utara, 2025)
This study explores the effectiveness of differentiated instruction based on students’ learning styles visual, auditory, and kinesthetic in teaching the water cycle to fifth-grade elementary students. Utilizing a quantitative approach with a quasi-experimental design, the research involved 27 students and assessed their learning outcomes through achievement tests. The differentiated instruction was tailored to individual learning preferences, ensuring students received content in formats most suited to their cognitive tendencies. The results showed that the average score (83.89) significantly exceeded the Minimum Mastery Criteria (75), with 74% of students categorized as having met the learning objectives. The findings underscore the importance of adapting instructional strategies to diverse learning styles to enhance student engagement and academic achievement, especially within the framework of the Merdeka Curriculum. The study concludes that differentiated instruction, when aligned with learning styles, can serve as an effective pedagogical model for science education in primary schools.